2014
DOI: 10.1186/1471-2164-15-365
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tissue transcriptomics of the black widow spider reveals expansions, co-options, and functional processes of the silk gland gene toolkit

Abstract: BackgroundSpiders (Order Araneae) are essential predators in every terrestrial ecosystem largely because they have evolved potent arsenals of silk and venom. Spider silks are high performance materials made almost entirely of proteins, and thus represent an ideal system for investigating genome level evolution of novel protein functions. However, genomic level resources remain limited for spiders.ResultsWe de novo assembled a transcriptome for the Western black widow (Latrodectus hesperus) from deeply sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 61 publications
9
103
0
Order By: Relevance
“…Previous experimental findings have suggested that spidroin expression is not exclusively gland specific [50][51][52][53][54] . Our RNA sequencing studies also suggested broader patterns of spidroin transcript expression across silk glands ( Supplementary Fig.…”
Section: Expression Profiling Of Individual Spidroins Across Multiplementioning
confidence: 93%
See 3 more Smart Citations
“…Previous experimental findings have suggested that spidroin expression is not exclusively gland specific [50][51][52][53][54] . Our RNA sequencing studies also suggested broader patterns of spidroin transcript expression across silk glands ( Supplementary Fig.…”
Section: Expression Profiling Of Individual Spidroins Across Multiplementioning
confidence: 93%
“…To identify non-spidroin candidate genes potentially involved in silk production, we cataloged transcripts that were (i) highly expressed and/or (ii) uniquely expressed in N. clavipes silk glands, resulting in a list of 649 candidates from our RNA sequencing data ( Supplementary Fig. 12 and Supplementary Table 15); 183 of these genes exhibited homology to documented silk gland-specific transcripts [50][51][52][53][54] . The candidates included catalytic enzymes such as kinases, proteases, dehydrogenases, acetyltransferases, and synthases, many of which are active in eukaryotic secretory systems 57 .…”
Section: Extreme Spidroin Diversity and Evolutionary Originsmentioning
confidence: 99%
See 2 more Smart Citations
“…57 Additionally, the analysis of RNA transcripts within silk glands has indicated a host of potential proteins that may be involved in silk biogenesis. 63,64 In particular, Clarke et al elegantly determined 647 silkgland specific transcripts for Latrodectus hesperus (western black widow) by removing transcripts also found in other spider tissues (venom and cephalothorax). Transcripts can be broadly categorized according to function and ranked according to the number of transcripts associated with that category.…”
Section: A Genes and Proteinsmentioning
confidence: 99%